2004
DOI: 10.1210/en.2004-0431
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Kisspeptins in the Regulation of Gonadotropin Secretion in the Mouse

Abstract: Kisspeptins are products of the KiSS-1 gene, which bind to a G protein-coupled receptor known as GPR54. Mutations or targeted disruptions in the GPR54 gene cause hypogonadotropic hypogonadism in humans and mice, suggesting that kisspeptin signaling may be important for the regulation of gonadotropin secretion. To examine the effects of kisspeptin-54 (metastin) and kisspeptin-10 (the biologically active C-terminal decapeptide) on gonadotropin secretion in the mouse, we administered the kisspeptins directly into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
775
1
31

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,033 publications
(838 citation statements)
references
References 29 publications
31
775
1
31
Order By: Relevance
“…For example, the immediate early gene, c-Fos, is expressed in GnRH neurons following kisspeptin administration (Irwig et al, 2004;Matsui et al, 2004). Additionally, the GnRH receptor antagonist, acyline, blocks gonadotropin release elicited by kisspeptin (Gottsch et al, 2004;Irwig et al, 2004;Shahab et al, 2005). A large proportion of GnRH cells co-express GPR54 mRNA, further supporting a direct mode of action by kisspeptin on GnRH neurons (Han et al, 2005;Irwig et al, 2004;Messager et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, the immediate early gene, c-Fos, is expressed in GnRH neurons following kisspeptin administration (Irwig et al, 2004;Matsui et al, 2004). Additionally, the GnRH receptor antagonist, acyline, blocks gonadotropin release elicited by kisspeptin (Gottsch et al, 2004;Irwig et al, 2004;Shahab et al, 2005). A large proportion of GnRH cells co-express GPR54 mRNA, further supporting a direct mode of action by kisspeptin on GnRH neurons (Han et al, 2005;Irwig et al, 2004;Messager et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…Hamsters were held in long-(n=12) or short-day (n=19) photoperiods for 8 weeks prior to kisspeptin injections. Animals were injected with either kisspeptin-10 [KiSS-1 (112-121)/metastin (45-54)(human); Phoenix Pharmaceuticals, Inc. Belmont, CA], a peptide known to stimulate GPR54 (Gottsch et al, 2004), or a 0.1 M PBS vehicle injection. Injections were given between 8.5 -11 h prior to lights out in LD animals and 4.5 -7.0 h before lights out in SD animals.…”
Section: Experiments 2: Endocrine Response To Exogenous Kisspeptinmentioning
confidence: 99%
“…Centrally administered kisspeptin stimulates GnRH neurons in the mouse, rat, sheep, and primate (Gottsch et al, 2004a;Irwig et al, 2004;Shahab et al, 2005). The integrity of the kisspeptin/GPR54 signaling system is necessary for normal reproduction.…”
Section: Kisspeptinmentioning
confidence: 99%
“…It had been demonstrated that in mice, kisspeptin neurons (i.e. those that express Kiss1 mRNA) are most numerous in the arcuate nucleus (Arc), but significant numbers are also seen in the periventricular nucleus (PeN) and the anteroventral periventricular nucleus (AVPV) (Gottsch et al, 2004a;Smith et al, 2005a,b). The Arc and AVPVare thought to play important roles in the feedback regulation of GnRH and gonadotropin secretion by estradiol and testosterone, however the exact circuitry that mediates this phenomenon is unclear (Kalra and Kalra, 1989).…”
Section: Kisspeptinmentioning
confidence: 99%
See 1 more Smart Citation